2022
DOI: 10.3389/fvets.2022.1066094
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic characterization of idiopathic epilepsy and epilepsy of unknown cause in Irish Setters

Abstract: Canine epileptic seizures are common neurological symptom presenting to veterinary practice. Idiopathic epilepsy (IE) with a suspected genetic background has been reported in several dog breeds. Although it has been reported in the Irish Setter (IS), the phenotypic characteristics have not yet been described. The aim of this study was to characterize the phenotype of IE in this breed and to trace its mode of inheritance.Owners of IS were requested to fill in a questionnaire via the Dutch Irish Setter Club conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Breeds like Beagles, British Alsatians, Keeshonds, Labrador retrievers, Golden retrievers, Boxers, Shetland sheepdogs, Vizslas, English Springer Spaniels, Irish wolfhoundsand Standard Poodles are supposed to develop epilepsy (Bielfelt et al, 1971;Jaggy et al, 1998;Patterson et al, 2003;Plonek et al, 2022). Heynold et al (1997) reported different aspects of epilepsy in labrador retrievers, which supports the findings of the present study, in which 33.33% (4/12) of dogs were Labrador retrievers.…”
Section: Resultssupporting
confidence: 87%
“…Breeds like Beagles, British Alsatians, Keeshonds, Labrador retrievers, Golden retrievers, Boxers, Shetland sheepdogs, Vizslas, English Springer Spaniels, Irish wolfhoundsand Standard Poodles are supposed to develop epilepsy (Bielfelt et al, 1971;Jaggy et al, 1998;Patterson et al, 2003;Plonek et al, 2022). Heynold et al (1997) reported different aspects of epilepsy in labrador retrievers, which supports the findings of the present study, in which 33.33% (4/12) of dogs were Labrador retrievers.…”
Section: Resultssupporting
confidence: 87%